A Framework for Technical Vocational Education and Training for Indigenous Peoples in the Philippines - Paul Omar Gangoso (PT FORMOSA CENDEKIA GLOBAL, 2023)
Technical education and vocational training (TVET) serves as a key strategy for raising employability of the Philippine labor force and reducing the polarity between skilled and non-skilled workers along with employed and unemployed graduates since the development of the Philippine Qualifications Framework. This study establishes a working model or a Competency-based TVET Framework for Indigenous Peoples in the Philippines. It will serve as an intervention paradigm that will guide TVET curriculum developers and policymakers in identifying and integrating theoretical and culturally appropriate disciplines into the curricular design of education and skills training for Indigenous Peoples. It will be a new framework, separate from but parallel to the current TVET Framework.